STUDI LIVING QUR’AN DALAM ANIMASI UPIN DAN IPIN: REPRESENTASI NASIHAT LUQMAN AL-HAKIM DEPISODE INDAHNYA RUMAH RASA SAYANG - Yahya, Yuangga Kurnia; Mahmudah, Umi (Living Islam: Journal of Islamic Discourses, 2024)
This research focuses on the representation of Luqman Hakim's advice in the animation Upin and Ipin episode "Indahnya Rumah Rasa Sayang" using Living Qur'an perspective. This research is a qualitative descriptive research based on literature sources. The data used in this study came from observation and documentation. The purpose of this study, firstly, is to analyze the verbal messages in the series and Luqman's advice to his son in Surah Luqman 12-19. Secondly, this study aimed to discuss the application of the living Qur'an in popular culture, especially films. The results of the study found seven pieces of advice on abstaining from surah Luqman verse 12-19 that appear in this episode. Those advices are 1) a commandment to always be grateful 2) orders always do good to parents 3) explain all human actions, good and bad 4) commanding prayers and commanding to do ma'ruf (good), prevent the evil, and be patient in dealing with various things happened 5) giving a smile and a cheerful face and not looking away from other people because of pride 6) equalize in behaving and speaking; 7) maintain good manners in interacting with others. Keyword: Surah Luqman; Upin and Ipin serial; Animation for Children; Living Qur’an   Penelitian ini bertujuan membahas tentang representasi nasihat Luqman Hakim dalam animasi Upin dan Ipin episode “Indahnya Rumah Rasa Sayang”: Perspektif Living Qur’an. Penelitian ini merupakan penelitian kualitatif deskriptif yang berbasis dari sumber-sumber pustaka. Data yang digunakan dalam penelitian ini berasal dari observasi dan dokumentasi dari tersebut. Tujuan penelitian ini yaitu, pertama menganalisis pesan-pesan verbal di serial tersebut dan nasihat Lukman kepada anaknya dalam Surah Luqman 12-19. Kedua, mendiskusikan aplikasi living qur’an dalam budaya populer, khususnya film.  Hasil penelitian menjelaskan terdapat tujuh nasihat penting yang terdapat surat Lukman ayat 12-19 yang diimplementasikan dalam tayangan ini, yaitu 1) perintah untuk selalu bersyukur; 2) perintah selalu berbuat baik kepada orang tua; 3) menjelaskan seluruh perbuatan manusia, baik dan buruknya; 4) perintah shalat, mengerjakan yang ma’ruf, mencegah kemunkaran, serta sabar terhadap berbagai hal yang menimpa; 5) memberikan senyuman dan wajah yang ceria serta tidak memalingkan wajah dari orang lain karena sombong; 6) sederhana dalam bertingkah laku dan berbicara; 7) menjaga budi bahasa dalam berinteraksi dengan orang lain. Kata kunci: Surah Luqman; Upin dan Ipin; Animasi Anak; Living Qur’an